Yield performance of forage shrubs and effects on milk production and chemical composition under the tropical climatic conditions of Peru - Durand Chávez, Luz Marlene; Vásquez Pérez, Héctor Vladimir; Ushiñahua Ramírez, Daniel; Carrasco Chilón, William Leoncio; Depaz Hizo, Benjamin Alberto; Saucedo Uriarte, José Américo (MDPI, 2023)
Forage shrubs have the potential to substantially contribute to pasture and increase the milk production of cows in tropical environments. The yield performance of forage shrubs and its effects on the production and chemical composition of milk in Bos indicus and Bos taurus crossbred cows in the tropics of Peru were studied. Fifteen cows were divided into M. alba, L. leucocephala, M. oleifera, and C. argentea treatments and only one of B. brizantha (control). Analysis of variance (p < 0.05) and comparison of means with Tukey’s test were performed. The highest plant height, stem diameter, fresh forage, and dry matter were observed in L. leucocephala and M. oleifera. The highest milk production was observed in cows fed B. brizantha with M. alba, and the highest milk production was in the rainy season. The highest concentration of fat and total solids was observed in milk from cows fed B. brizantha with L. leucocephala. The highest utility was observed in cows fed B. brizantha with M. alba; however, the highest operational profitability was observed in the treatment of only B. brizantha and B. brizantha with L. leucocephala. The use of forage shrubs can contribute to cattle feeding, especially in the dry season when there is a shortage of pastures, and possibly contribute to improving the soil and overcoming climate change.